2017
DOI: 10.1371/journal.pone.0174082
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial correlates of nutritional status among people living with HIV on antiretroviral therapy: A matched case-control study in Central zone of Tigray, Northern Ethiopia

Abstract: BackgroundMalnutrition hastens progression to Acquired Human Immunodeficiency Syndromes (AIDS) related illnesses; undermines adherence and response to antiretroviral therapy (ART) in resource-poor settings. However, nutritional status of people living with HIV (PLHIV) can be affected by various psychosocial factors which have not been well explored in Ethiopia. Therefore, the objective of this study was to determine psychosocial correlates of nutritional status among people living with HIV (PLHIV) on ART in Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 55 publications
5
30
0
Order By: Relevance
“…Other finding was people living with HIV on ART having below average monthly income (mean � 1200 ETB) had higher odds of cases. is is in line with a study done in Kenya [31], Tigray Region, Ethiopia [32], Democratic Republic of Congo [33], Uganda [34], Dilla University Referral Hospital, Ethiopia [7], and Zimbabwe [29] which indicates that poor socioeconomic factors leads to lack of access to food and is associated with undernutrition among people living with HIV enrolled on antiretroviral treatment.…”
Section: Discussionsupporting
confidence: 91%
“…Other finding was people living with HIV on ART having below average monthly income (mean � 1200 ETB) had higher odds of cases. is is in line with a study done in Kenya [31], Tigray Region, Ethiopia [32], Democratic Republic of Congo [33], Uganda [34], Dilla University Referral Hospital, Ethiopia [7], and Zimbabwe [29] which indicates that poor socioeconomic factors leads to lack of access to food and is associated with undernutrition among people living with HIV enrolled on antiretroviral treatment.…”
Section: Discussionsupporting
confidence: 91%
“…The strong association that we found between ART adherence and undernutrition is also fairly well established [3,12,15,24] and in keeping with other recent studies in sub-Saharan Africa [43] that find a relationships between food insecurity, undernutrition, and difficulties in patient adherence and treatment initiation [14]. Several studies have found that concerns about having an adequate amount of food might people to stop or delay treatment [7,15,17].…”
Section: Discussionsupporting
confidence: 89%
“…We found no association between undernutrition, educational level, urban residence, home ownership and access to public municipal goods such as electricity and piped water. Wealth or income of patients on ART has been found to be negatively associated with undernutrition in Haiti [54], and Brazil [55], as was educational status in Senegal [19] and wealth in Tigray, Ethiopia [43]. The lack of association may reflect the largely urban make up of our sample or simply the weakness of these measures in capturing socio-economic status.…”
Section: Discussionmentioning
confidence: 82%
“…In similar with the findings of other studies in Ethiopia (Berhe, Tegabu & Alemayehu, 2013), the current study found malnourished PLWHA were non-adherent to ART. This is also reported in another matched case-control study in the Central Tigray Zone, Ethiopia that revealed malnutrition was among the independent factors associated with lack of adherence to ART (Weldehaweria et al, 2017). Absence of nutritional support fuels the synergistic co-existence of HIV and malnutrition that has a perverse effect on ART adherence and the wellbeing of PLWHA (Mekuria et al, 2015;Sicotte et al, 2014;Berhe, Tegabu & Alemayehu, 2013).…”
Section: Discussionsupporting
confidence: 59%